Identifying and Supporting the Needs of Internal Medicine and Pediatrics Residents Interested in Pediatric Hospital Medicine Fellowship. Issue 9 (18th August 2021) - Boggs, Elizabeth; Luttrell, Harrison; Basco, William; Brittan, Mark; Jerardi, Karen; Kessenich, Jeri; Kondos, Valien; O'Toole, Jennifer; Solomon, Jeffrey; Tarchichi, Tony; Jenkins, Ashley
Abstract : BACKGROUND: Pediatric hospital medicine (PHM) became a subspecialty of the American Board of Pediatrics (ABP) in 2016. Starting in 2019, residency graduates are required to complete fellowship training to qualify for PHM board eligibility. These requirements pose unique challenges to internal medicine–pediatrics (med‐peds) residents interested in practicing combined adult hospital medicine (HM) and PHM. OBJECTIVE: To describe the needs of med‐peds residents interested in PHM fellowship training and how the current PHM training environment can meet these needs. METHODS: We conducted two cross‐sectional electronic survey studies: one of med‐peds residents and one of PHM fellowship program directors (FDs). Surveys were distributed to resident and FD listservs. Questions were designed using an iterative consensus process among authors. Responses were analyzed with descriptive statistics. RESULTS: Four hundred sixty‐six residents responded to the resident survey. Ninety‐six percent (n = 446) had considered a career in HM. Almost all (n = 456, 97.9%) respondents indicated a preference for a fellowship with both adult HM and PHM clinical training. Subspecialty designation decreased desire to pursue a career including PHM for 90.1% of respondents. Twenty‐eight (58.3%) FDs responded to the FD survey. Fifteen (53.6%) programs reported being able to accommodate adult HM and PHM clinical time. CONCLUSION: The majority of resident respondents reported a desire for a PHM fellowship with clinical time in both PHM and adult HM. Approximately 30% of current US PHM fellowship programs can accommodate adult HM practice for med‐peds fellows, and many other programs would be willing to explore such opportunities.